Membangun Kesadaran Siswa tentang Pentingnya Pendidikan Kewarganegaraan di Era Digital - Saqinah Aifi Kirmala; Angela Eva Nia; Arini Rehulina Surbakti; Solavide Ginting; Sri Yunita (Public Service and Governance Journal, 2024)
Citizenship education is important to teach students and young people the values ​​and skills of being active citizens. The aim of this research is to build student character who is developing in the current digital era. This research uses a qualitative method with a literature study approach. The data collection technique used is through literature analysis, such as books, scientific articles, and various sources relevant to this research, namely building student awareness about the importance of citizenship education in the digital era. In the current digital era, citizenship education is very important as a control tool in accepting change so that students do not lose their identity in realizing the golden generation of the Indonesian nation. The role of technology as a means to make it easier to teach civics education to students. With the help of various supports such as parents, teachers, government and society. Apart from being students, students must also become citizens who have a sense of nationalism and defend the country, by applying Pancasila values, be active in the democratic political process, and be able to encourage the surrounding community as agents of change. The challenge of using technology as an educational tool is that students are easily influenced by fake news, not all students have devices and internet connections, students and teaching staff still lack skills in implementing IT (Information Technology). By linking citizenship education to digitalization, it will be easier to provide teaching because students can explore diversity which is quite minimal if we get information directly, then students can find out about the diversity that exists in Indonesia and the world.